Sustainable Development Goals Through Carbon Dioxide Conversion to Formic Acid as Coagulation Agent - Nikolas Ardian Prihantoro; Puspita Nurlilasari (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
Addressing global sustainability challenges requires innovative approaches that integrate environmental, economic, and technological solutions. This article explores the sustainable development potential of converting carbon dioxide (CO₂), a major greenhouse gas, into formic acid—a valuable chemical compound used as a freezing agent in the coagulation of natural rubber. The study further delves into the solid-state characteristics of materials involved in this process, emphasizing the distinction between crystalline and amorphous solids. Understanding the atomic arrangement in materials contributes to optimizing coagulation and freezing techniques critical for natural rubber production. This work links CO₂ valorization with advanced material science principles, promoting circular economy and environmental sustainability aligned with the United Nations Sustainable Development Goals (SDGs).